National survey of gestational age and birth weight limit for direct admission to postnatal ward after birth. (7th June 2011) - Arora, P K; Price, R; Fleming, P; Aladangady, N
Abstract : Aim: To conduct national survey of admission practice for near term and low birth weight (B Wt) infants directly to postnatal ward (PNW) after birth. Method: All Neonatal Units in England contacted over the telephone and collected the data. Results 184 neonatal units in England were contacted and 180 responded (98%). Of the four non-responders two were from Level 1, and one each from Level 2 and Level 3 units. The details of neonatal units, gestational age (GA) & B Wt limit for direct PNW admission after birth are presented in table 1 . Significantly lower gestational age infants were admitted directly to PNW in Level 2 units compared to Level 1 (p 0.03; CI 0.03 to 0.52) and Level 3 units compared to Level 2 (p 0.02; CI 0.028 to 0.211). Mean B Wt limit for direct PNW admission was significantly lower in Level 3 units compared to Level 1 (p 0.011; CI 0.028 to 0.211). Conclusion: Type of neonatal unit influences the lower limit of B Wt & gestational age of near term infants admitted directly to PNW after birth.